Meta-analysis: The effectiveness of the integrated STEM technology pedagogical content knowledge learning model on the 21st century skills of high school students in the science department - Zulkifli Zulkifli; Agus Supriyadi; Erwinsyah Satria; Tomi Apra Santosa (Psychology, Evaluation, and Technology in Educational Research, 2022)
This study aims to analyze the effect of the STEM integrated Technology Pedagogical Content Knowledge learning model on the 21st Century skills of high school students majoring in science. This research is a type of meta-analysis research. The sample of this research comes from the analysis of international and national journals indexed by Scopus, SINTA, and DOAJ, totaling 12 journals. The sample search was carried out by searching the google scholar database, Sciencedirect, Eric Journal, Taylor and Francis, Wiley Journal, Sage Journal, and Emerald. The sampling technique is purposive sampling technique. The data that can be sampled is related to the STEM-integrated TPACK learning model in 21st Century Student skills. The data analysis technique is a quantitative data analysis technique by calculating the Effect Size (ES) and N-Gain values ​​with JSAP software. The results of the study conclude that the application of the integrated STEM Technology Pedagogical Content Knowledge learning model is effective in improving the 21st-century skills of high school students with an effect size value of 1.765 with an N-Gain of 0.56 and an SD value of 0.29. So, the STEM-integrated TPACK learning model is very effectively applied in high school biology learning